(untitled) (International Association of Biologicals and Computational Digest, 2023)
In today’s world, people are focusing more towards a healthy lifestyle. One of the most important elements for the human body is Protein. A majority part of earth’s ecosystem comprises of protein. This study presents the estimation of protein conducted in four different legume species namely, Chick pea, Alfa alfa, Black gram, and Pea in different growth media such as, Chemical fertiliser, Goat manure and Cow-dung manure. Samples of all the species were randomly selected from all the sets of growth media for protein estimation through spectrophotometry and compared it with standard BSA. The experiment showed high protein content in organic fertilisers such as Goat manure and Cow-dung manure. The growth medium of Chemical fertiliser showed poor protein content in all the samples.